Influence of Co-Sputtered Ag:Al Ultra-Thin Layers in Transparent V2O5/Ag:Al/AZO Hole-Selective Electrodes for Silicon Solar Cells - Thomas Tom (Materials, 2020)
As optoelectronic devices continue to improve, control over film thickness has become crucial, especially in applications that require ultra-thin films. A variety of undesired effects may arise depending on the specific growth mechanism of each material, for instance a percolation threshold thickness is present in Volmer-Webber growth of materials such as silver. In this paper, we explore the introduction of aluminum in silver films as a mechanism to grow ultrathin metallic films of high transparency and low sheet resistance, suitable for many optoelectronic applications. Furthermore, we implemented such ultra-thin metallic films in Dielectric/Metal/Dielectric (DMD) structures based on Aluminum-doped Zinc Oxide (AZO) as the dielectric with an ultra-thin silver aluminum (Ag:Al) metallic interlayer. The multilayer structures were deposited by magnetron sputtering, which offers an industrial advantage and superior reliability over thermally evaporated DMDs. Finally, we tested the optimized DMD structures as a front contact for n-type silicon solar cells by introducing a hole-selective vanadium pentoxide (V2O5) dielectric layer.